Occupational therapy’s oversight: How science veiled our humanity - Heleen Reid; Clare Hocking; Elizabeth Smythe (Scandinavian Journal of Occupational Therapy)
Background Occupational therapy’s connection to positivist science predates the profession’s formal beginning, with important contributing knowledge sources coming from mathematics, physics, psychology, and systems theory. While these sources of objective knowledge provide a rational, defendable position for practice, they can only explain a portion of what it means to exist as an occupational being.Aims/Objectives This article aims to reveal some of the history of science within occupational therapy and reveal the subjective, ontological nature of doing everyday activities that the profession’s preoccupation with positivist science has obscured.Methods This research used a history of ideas methodology to uncover how occupational therapy perceived people and how practice was conceptualised and conducted between 1800 and 1980s, as depicted in writing of the time.Conclusion Analysis showed that, through history, people were increasingly categorised and delimited. Practice also became systematically controlled, moving occupational therapy into a theoretical, scientific, and abstract realm.Significance The emphasis placed on objectivity diminishes the attention given to human ways of practicing, where the subjective experience is central to our thinking.